Good Manners in Sport and Sports Culture - Prerequisite for Combating Sports Violence - Stojanoska Ivanova, Tatjana; Anastasovski, Ivan; Frichand, Ana; Damovska, Lena (Филозофски факултет, Скопје, 2016)
Sports as a game, as someone’s professional orientation, as a manner of proper and desired spending of leisure time, is a phenomenon which primarily involves positive social discourse. Unfortunately, the reality shows that in recent years the sporting events have become an arena for violence and aggressive behaviour, both on part of the direct actors - sportsmen and referees - and on part of the supporter’s groups. In order to overcome this situation and to stop the violence on the sports grounds, the research studies that have been regularly conducted suggest that one of the most desirable and effective way of preventing sports violence is to strengthen the sports culture and the good manners in sport.. The point of real sport lovers is by spreading the sports culture and the good manners in sport to practice all norms and values that shall contribute towards overcoming the negative social phenomena during sporting events.
Keywords: sporting events, violence, aggression, good manners in sport, sports culture